Sodoma e Gomorra: Cronistoria del Libertinaggio attraverso i secoli ed il mondo - Docteur Jaf; Fabiani, P. (Pietro) (Salt Lake City, UT : Project Gutenberg, 2011)
"Sodoma e Gomorra: Cronistoria del Libertinaggio attraverso i secoli ed il mondo" is a historical account likely written in the late 19th century. This work examines the history and evolution of debauchery, tracing its manifestations from ancient civilizations to modern times. The book likely delves into various cultural practices related to libertinism, focusing on historical figures and societies that exemplified such behaviors. The opening of the book sets the tone for a comprehensive exploration of sexual immorality. It begins by referencing the biblical tales of Sodom and Gomorrah as metaphors for human corruption, suggesting that such moral failings have deep historical roots. The author outlines the various practices surrounding worship of the goddess Venus in ancient cultures, illustrating how these customs gave rise to various forms of libertinism through the ages. The text emphasizes the universality of such vices by presenting examples from different cultures, including Babylonia and ancient Rome, and critiques the actions of notable historical figures alongside communal practices, creating a detailed narrative on the longstanding history of sexual permissiveness and moral decay. (This is an automatically generated summary.)
Release date is 2011-10-16
Produced by Enrico Segre and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Vice; Sex customs -- History